Representasi Perempuan dalam Pemilihan Bupati dan Wakil Bupati Serentak di Jawa Tengah Tahun 2015 - Marwah, Sofa (Jurnal Politik, 2016)
The reform era has been a space for presenting women in politics. In this case, the political constellation in the head of district elections could not be separated from expectations to increase political participation of women in public offices. In contrast to the Election Law that had set a quota of 30% affirmative policies for women, the Law No. 8 Year 2015 on the election of Governor and Head of Cities and Regent is neutral because it allows women and men to compete openly. In fact, based on the simultaneous head of regency election in 21 regencies/cities in Central Java, from 56 pairs of candidates who competed, the number of pairs which one of the partners is women, are only 15 pairs. Women who are elected are three heads of regency and 6 vices of regency. Nevertheless, the success of women as head of regencies in Grobogan, Kendal, and Klaten at least are able to represent the ability of women in public office. In the spirit of political equality, the provision of the nomination of governor or vice of governor, head or vice of regency or city by political parties, in which one of the partner must be female, may be considered as an affirmative policy in the future.